Intrapreneurship: facilitating and limiting factors for its development in organizations - Aranibar Ramos, Edgar Romario (2022)
Intrapreneurship represents the initiative of employees in organizations, and for the sake of sustainability, its analysis is relevant. Due to this, this work intends to delve into the main facilitating and limiting factors of the development of intrapreneurship in organizations, using for such purposes a qualitative, descriptive, non-experimental methodology based on a review of primary and secondary, national and international sources. It was concluded from them that both facilitating and limiting factors can be segmented into four types: personal, social-environmental, economic-financial and technological. Thus, within the facilitating factors, there was found a positive link and compatibility with the organization, a good work environment, assertive communication and recognition, availability of resources, possession of digital devices and technical knowledge. On the other hand, there was found personal and organizational incompatibility, bureaucracy, difficulty in accessing resources and lack of tangible technology and technical knowledge. Additionally, some intrapreneurship contributions were recognized as a result of the factors addressed. Finally, intrapreneurship studies are recommended from a local, regional and gender perspective.